Understanding job expectation and its differences on the individual level - Ma, Jie (2019)
This study aimed at understanding the landscape of individuals’ job expectation, which was actualised by investigating people’s most desired job characteristics and evaluating differences on the individual level in their expectations. Data was collected from 218 valid questionnaires that were distributed by online surveys toward Chinses management professionals. The theoretical basis of this study was developed by the theories of met expectation, psychological contract, and motivation, which enhanced the significance of this research and guided this study profoundly. The main findings can be divided into two parts, including the individuals’ desired job characteristic and the individual differences in job expectation. On the one hand, the job characteristics related to Rewarding was considered as the most important job attributes. On a more micro level, Satisfactory salary and benefits, Job promotion opportunities and Financial reward were the top three elements that individuals desired toward a job. On the other hand, the findings of difference tests showed significant differences on the individual level, in detail, gender, education background and work experience can be the factors on the personal level, which resulted in the discrepancy in individuals’ job expectation on various dimensions. Furthermore, through the profound analysis, the potential reasons for the findings were tried to be identified. It helped to give possible suggestions for HR practitioners to conduct better managerial strategies, for example, the recommendations for better managing individuals’ expectation during the recruitment process. Finally, the limitations of this research were reflected at the end of this paper, which can provide possible recommendations for scholars who will do future studies in this research field.